Delayed Surgical Reconstruction of Chronic Fourth-Degree Perineal Laceration: Impact on Female Sexual Function - A Case Report - Hasanuddin; Roziana; Zahara, Fatimah (Journal of International Surgery and Clinical Medicine, 2025)
Introduction : Among the gravest complications occurring during childbirth are fourth-degree perineal lacerations, characterized by complete disruption of the anal sphincter mechanism with potential for persistent sequelae including fecal incontinence and impaired sexual health. These traumatic injuries profoundly compromise women's wellbeing, with sexual health disturbances documented in 30-60% of affected women three months following delivery. The Female Sexual Function Index (FSFI) provides validated assessment across six critical dimensions: libido, arousal capacity, vaginal lubrication, orgasmic function, overall satisfaction, and dyspareunia. Case presentation: We present the clinical course of a 33 year old multiparous woman who sought consultation nine months postpartum with chronic fourth-degree perineal disruption accompanied by anal incontinence and sexual dysfunction. Initial FSFI assessment revealed a score of 16.2, demonstrating substantial sexual impairment. Surgical intervention employed a comprehensive ten-stage reconstruction protocol involving systematic restoration of anal mucosa, internal and external sphincter components, vaginal wall integrity, and perineal tissue architecture. At five-month postoperative evaluation, the patient exhibited complete continence restoration and remarkable sexual function recovery, with FSFI scoring advancing to 28.0, indicating normalization of sexual health parameters. Quality of life indicators demonstrated meaningful enhancement across all assessed dimensions. Conclusion: Secondary reconstruction of chronic fourth-degree perineal disruptions can successfully restore both continence mechanisms and sexual function when executed using meticulous surgical methodology. Prompt recognition and appropriate timing of intervention remain paramount for achieving optimal patient outcomes and restoring quality of life.